Arrhythmias and Adaptations of the Cardiac Conduction System in Former National Football League Players. Issue 15 (6th August 2019) - Aagaard, Philip; Sharma, Shishir; McNamara, David A.; Joshi, Parag; Ayers, Colby R.; de Lemos, James A.; Lincoln, Andrew E.; Baranowski, Bryan; Mandsager, Kyle; Hill, Elizabeth; Castle, Lon; Gentry, James; et al.
Abstract : Background: Habitual high‐intensity endurance exercise is associated with increased atrial fibrillation (AF) risk and impaired cardiac conduction. It is unknown whether these observations extend to prior strength‐type sports exposure. The primary aim of this study was to compare AF prevalence in former National Football League (NFL) athletes to population‐based controls. The secondary aim was to characterize other conduction system parameters. Methods and Results: This cross‐sectional study compared former NFL athletes (n=460, age 56±12 years, black 47%) with population‐based controls of similar age and racial composition from the cardiovascular cohort Dallas Heart Study‐2 (n=925, age 54±9 years, black 53%). AF was present in 28 individuals (n=23 [5%] in the NFL group; n=5 [0.5%] in the control group). After controlling for other cardiovascular risk factors in multivariable regression analysis, former NFL participation remained associated with a 5.7 (95% CI: 2.1–15.9, P <0.001) higher odds ratio of AF. Older age, higher body mass index, and nonblack race were also independently associated with higher odds ratio of AF, while hypertension and diabetes mellitus were not. AF was previously undiagnosed in 15/23 of the former NFL players. Previously undiagnosed NFL players were rate controlled and asymptomatic, but 80% had a CHA2 DS2 ‐VASc score ≥1. Former NFL players also had an 8‐fold higher prevalence of paced cardiac rhythms (2.0% versus 0.25%, P <0.01), compared with controls. Furthermore, former athletes had lower resting heart rates (62±11 versus 66±11 beats per minute, P <0.001), and a higher prevalence of first‐degree atrioventricular block (18% versus 9%, P <0.001). Conclusions: Former NFL participation was associated with an increased AF prevalence and slowed cardiac conduction when compared with a population‐based control group. Former NFL athletes who screened positive for AF were generally rate controlled and asymptomatic, but 80% should have been considered for anticoagulation based on their stroke risk.